Plant-Based Diets for the Prevention and Treatment of Disabling Diseases. (September 2015) - Greger, Michael
Overestimates of the efficacy of surgical and pharmacological interventions for the prevention and treatment of chronic disease and underestimates of the associated risks may bias physicians and patients against lifestyle medicine interventions that can be cheaper, safer, and more effective by treating the underlying cause of disease. The leading causes of both death and disability in the United States are diet, followed by smoking. The food and tobacco industries share similar tactics to downplay and obfuscate the risks associated with their products, but physicians can educate themselves about the role lifestyle interventions can play in the prevention and treatment of chronic disease. For example, a diet centered around whole plant foods can be used to successfully treat angina and painful diabetic neuropathy and may help prevent low-back pain and Alzheimer's disease, all perhaps because of a common underlying vascular component. The delay between recognizing the risks of smoking and effective public health measures may have cost millions of lives. Similar delays in stopping dietary diseases may cost millions more.